Comparative Analysis of Windows and Linux Operating Systems for Secondary School Laboratories: A Limited Systematic Literature Review - Zaehol Fatah; Aisyah Putri Sabrina (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Operating systems determine the day-to-day sustainability of school computer labs — particularly when institutions face licensing budget constraints, varying device specifications, and basic security requirements. This article is structured as a limited systematic literature review comparing Windows and Linux in an educational context, without claiming to be a primary benchmark experiment. The methodology follows PRISMA 2020 and Kitchenham systematic literature review guidelines, covering research question formulation, literature search, inclusion-exclusion criteria-based selection, quality assessment, and thematic synthesis. From an initial pool of 68 records, 10 relevant and traceable sources were used as the basis for synthesis across five core dimensions: licensing cost, hardware requirements, application compatibility, security, and user readiness. The findings indicate that while Linux presents strict user privilege execution layers and zero direct licensing overhead, Windows demonstrates superior native compatibility with proprietary national examination client browsers and a shorter learning curve due to established user familiarity. This article contributes a multi-criteria decision matrix for educational labs that balances operational constraints against technical efficiency.